Granting of Mortgage Loans With Guarantees of Land Right Owned by Third Parties in Banking Agreements - Cahya Khaerani; Budi Santoso; Hanif Nurwidhiyanti (Jurnal IUS Kajian Hukum dan Keadilan, 2022)
This study aims to analyze the process of implementing an agreement between a bank and a third party as a collateral owner/which does not belong directly to the debtor, and analyze the legal protection for the owner of the object of mortgage rights pledged by the debtor. The method of approach used in this research is the juridical empirical approaching method. In the implementation of the agreement between the Bank and the collateral owner third party, it is carried out through the Mortgage Rights mechanism. In the event of default by the debtor. Then, the creditor (bank) can still execute the object of collateral pledged by the debtor in accordance with applicable regulations. Second, the UUHT does not provide enough protection to the collateral owner/third party, considering that the third party/collateral owner is not the direct debtor in the credit agreement. In addition, between the third party and the creditor (Bank) also do not have a direct legal relationship, because the third party only has a direct legal relationship with the debtor. So that the third party will only get legal protection from the debtor in accordance with the agreement made with the third party.